Effect of Therapeutic Ultrasound on Histomorphometeric Features of Tibia of Rats (Medical Forum Monthly, 2022)
Objective: To evaluate the effects of duration of its exposure on healthy bone.Study Design: Experimental study.Place and Duration of Study: This study was conducted at the Department of Physiotherapy Ziauddin University, Karachi from April 2021 to June 2021 for a period of 8 weeks.Materials and Methods: Total of 18 rats were enrolled in this study (6 rats in each group). Group A was the control group, whereas groups B and C were given 10 minutes and 20 minutes of ultrasound at 1.5 MHz frequency respectively for 14 days. All rats were sacrificed next day using standard protocols and data was analyzed using SPSS version 25.Results: Our study showed statically significant decrease (p-value 0.003) in mean number of osteon per hpf ( 6 in both group A and B while 2.3 in group C) and in mean number of lamellae (13.1 in group A, 12.8 in group B and 3.3 in group C )as the duration of ultrasound increased. Area of haversion canal and area of osteon showed statically significant increase (p-value 0.027 and 0.002 respectively) as the duration of therapeutic ultrasound increased. Mean area of haversion canal in group A, B and C were 37.6 μm2, 37.3 μm2 and 59.3 μm2 respectively. Mean osteon area in group A, B and C were 311.2 μm2, 266.9 μm2 and 230 μm2 respectively.Conclusion: Use of therapeutic ultrasound on healthy bone showed damage to bone histology by decreasing the number of osteons, osteon area and number of lamellae and increase in area of haversion canal.